Charting the global footprint of borderline oxacillin-resistant Staphylococcus aureus (BORSA): the first systematic review and meta-analysis - Engku Abd Rahman, Engku Nur Syafirah; Irekeola, Ahmad Adebayo; Yamin, Dina; Elmi, Abdirahman Hussein; Chan, Yean Yean (PeerJ, 2024)
Borderline oxacillin-resistant Staphylococcus aureus (BORSA) has been a persistent yet under-researched concern in the realm of antibiotic resistance, characterized by unique resistance mechanisms and potential for severe infections. This systematic review and meta-analysis consolidates data from 29 studies encompassing 18,781 samples, revealing a global BORSA prevalence of 6.6% (95% CI [4.0–10.7]). The highest prevalence was found in animals (46.3%), followed by food (8.9%), and humans (5.1%). Notably, significant regional disparities were observed, with Brazil exhibiting the highest prevalence at 70.0%, while The Netherlands reported just 0.5%. These findings underscore the multifaceted nature of BORSA epidemiology, influenced by local antibiotic usage practices and healthcare infrastructures. The analysis also reveals substantial heterogeneity (I2 = 96.802%), highlighting the need for improved reporting practices and tailored surveillance protocols that account for the specific contexts of each study. As antibiotic resistance continues to escalate, understanding BORSA’s global footprint is crucial for informing targeted interventions and optimizing antibiotic stewardship programs. This study fills critical gaps in current knowledge of BORSA and highlights the need for coordinated efforts among researchers, healthcare providers, and policymakers to develop effective strategies for addressing the rising threat of antibiotic-resistant pathogens like BORSA, including further exploration of its genetic and phenotypic characteristics.
Keywords: Staphylococcus aureus; Borderline; Oxacillin-resistant; BORSA